2015
DOI: 10.1109/ted.2015.2478807
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effect of Postannealing Time on Positive Bias Stress Stability of In–Ga–Zn–O TFT by Conductance Method

Abstract: The conductance method was used to investigate the positive bias stress (PBS) degradation mechanism of In-Ga-Zn-O (IGZO) thin-film transistor (TFT). The effects of postannealing time on the PBS degradation mechanism were investigated. The stabilization of the donorlike interface defects was found to be the reason for the threshold voltage instability in the IGZO-TFT under the PBS test. The donorlike defects at the front channel interface and in the plasma-enhanced chemical vapor deposition (PE-CVD) SiO x acted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…where L is the channel length, and ϕ sd and ϕ ss are the value of ϕ s when V ch = V DS and V ch = 0 V, respectively. In Equation (11), the integral result of Q i (ϕ s ) can be written as…”
Section: Model Calculation 21 Surface Potential Model Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…where L is the channel length, and ϕ sd and ϕ ss are the value of ϕ s when V ch = V DS and V ch = 0 V, respectively. In Equation (11), the integral result of Q i (ϕ s ) can be written as…”
Section: Model Calculation 21 Surface Potential Model Calculationmentioning
confidence: 99%
“…Although the bandtail states and localized deep states are considered in these models for a-IGZO TFTs, the localized sub-gap density of states (DOSs) is invaluable in solving the model. Actually, new defects are generated in the device channel or at the a-IGZO/gate dielectric interface under external stress conditions [10,11]. For example, it has been demonstrated that the oxygen interstitial (O i )-related defects are created in the device channel or the interface region under gate bias stress, originating from weakly bonded oxygen ions in a-IGZO TFTs [12,13].…”
Section: Introductionmentioning
confidence: 99%